Synthesis of quinoxaline dioxocyclams, analysis of their DNA binding and cleaving properties and progress toward the synthesis of ruthenium(II) terpyridine capped dioxocyclams - Wendling, Jory James, author; Hegedus, Louis S., advisor; Finke, Richard G., committee member; Strauss, Steven H., committee member; Shi, Yian, committee member; Suchman, Erica L., committee member (Colorado State University. Libraries, 2003)
A new class of dioxocyclams containing appended quinoxaline chromophores linked in various spacial orientations were synthesized and tested for their ability to bisintercalate and oxidatively cleave plasmid DNA. The circular-DNA unwinding test revealed no evidence for bisintercalation with either the dioxocyclams or their nickel(II) complexes. However, the DNA cleaving ability of these complexes was found to be directly dependent upon both the nature and spacial orientation of the appended quinoxaline moieties. These results imply at least a transient association of the nickel(II) complexes with DNA. Progress was made in the synthesis of a new class of dioxocyclam structures. These structures feature a terpyradine moiety appended to a "capped" dioxocyclam. Eventually, a variety of metals will be incorporated into these systems and they will be tested for their electrical, magnetic, and photochemical properties.
Keywords: organic chemistry